The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/en13071832
|View full text |Cite
|
Sign up to set email alerts
|

Fluid–Structure Interaction Numerical Analysis of a Small, Urban Wind Turbine Blade

Abstract: While the vast majority of the wind energy market is dominated by megawatt-size wind turbines, the increasing importance of distributed electricity generation gives way to small, personal-size installations. Due to their situation at relatively low heights and above-ground levels, they are forced to operate in a low energy-density environment, hence the important role of rotor optimization and flow studies. In addition, the small wind turbine operation close to human habitats emphasizes the need to ensure the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…Because the pressure variation around the blade for the considered wind speed (v = 4 m/s) was less than 100 Pa, the two-way coupling, where the pressure load on blades would be transferred from the flow to the structural analysis, was disregarded. The one-way system coupling method was successfully used and presented in [27]. Due to the complexity of blade deformations, combined with their rotation, a tool outside the fluid flow solver was needed to define the instantaneous rotor geometry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the pressure variation around the blade for the considered wind speed (v = 4 m/s) was less than 100 Pa, the two-way coupling, where the pressure load on blades would be transferred from the flow to the structural analysis, was disregarded. The one-way system coupling method was successfully used and presented in [27]. Due to the complexity of blade deformations, combined with their rotation, a tool outside the fluid flow solver was needed to define the instantaneous rotor geometry.…”
Section: Methodsmentioning
confidence: 99%
“…The FSI is a very wide concept of solvers coupling in order to obtain high-fidelity numerical solutions. Solvers can be one-way coupled once the data, i.e., loads from the fluid acting on the wall, are transferred to the structural solver where stress and strains are determined [27,28]. Another example of one-way coupling takes place where the deformation of the structure influences the flow structure and loads determined in the fluid solver.…”
Section: Introductionmentioning
confidence: 99%
“…This editorial provides a swift archetype of a wind turbine with the required parameters by providing numerical models of a wind turbine rotor [ 28 ]. A 3D printing method was used, and the product was tested in a domestic wind tunnel.…”
Section: Introductionmentioning
confidence: 99%
“…Based on discussions of blade deformation and stress, fluid–structure interaction research of wind blades was conducted [ 7 ]. The angle of attack and wind speed of the three different airfoils—S811, S822 and S826—used to produce the three and five-blade configurations, based on structural steel and aluminum alloy, were analyzed [ 8 ]. A 750 kW horizontal axis wind turbine system made of E-glass/epoxy composite material-based wind blades were designed and analyzed, where it was found that the proposed blade has a number of advantages over the ones currently in use, including safety, stability under a variety of stress conditions, and resistance to a variety of loads, including aerodynamic loads, ice build-up loads, hydrothermal loads, and mechanical loads [ 9 ].…”
Section: Introductionmentioning
confidence: 99%